PENGARUH PROFESIONALISME KERJA PEGAWAI TERHADAP KUALITAS PELAYANAN PUBLIK DI KABUPATEN KOLAKA UTARA - Khatimah, Ridha Khusnul; Hakim, Lukman; Ma'ruf, Adnan (Universitas Muhammadiyah Makassar, 2024)
This study aims to determine the effect of employee professionalism on the quality of public services at the population and civil registration services in Kolaka Utara district. The main problem in this research is that the writer finds that the level of work professionalism is not entirely good. The type of research used is quantitative research that aims to describe the object of research or research results through data or samples, the data collection techniques used are observation, questionnaires and documentation. The method in this study used a simple regression analysis method with hypothesis testing, namely the T test. The number of samples was 50 people using the Incidental Sampling Technique Method. Based on the statistical results of the t-test for the variable employee work professionalism, a significance level of 2.699 r^table 0.278 was obtained which succeeded in proving that